Helminth communities from amphibians inhabiting agroecosystems in the Pampean Region (Argentina) - Draghi, Regina (2020)
The objectives of this study were to describe the composition and infection patterns of the helminth communities associated with four amphibians (P. minuta, B. pulchella, L. latrans and R. fernandezae) with different life-habits, and additionally to compare the helmith fauna associated with these amphibians in agroecosystems with different land use (crops and livestock). A total of 300 anuran individuals and twelve helminth taxa were collected in sites located northeast of the Province of Buenos Aires, Argentina. Helminth communities differed between amphibian species according to their habitat preference, digeneans were predominant in aquatic and arboreal amphibians (Hylidae) and nematodes with direct life cycle were found parasitizing semi-aquatic and terrestrial amphibians (Leptodactylidae and Bufonidae). In three of the frog species (B. pulchella, L. latrans and R. fernandezae), parasite prevalence did not vary significantly according to land use. The values of abundance and infracommunity species richness, meanwhile, varied according to land use, with the highest abundance values in crop sites and higher richness in livestock sites. Regardless of the use of land, L. latrans presented the highest values of prevalence, abundance, and richness of helminth species. This is the first study assessing the ecological aspects of parasite taxa in populations of P. minuta, B. pulchella and L. latrans that inhabit agroecosystems in Argentina.